Mali : 2018 Article IV Consultation and Eighth and Ninth Reviews Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Mali's economic recovery continued in 2017 amid persistent security challenges. GDP growth remained robust, at an estimated 5.3 percent supported by good harvests and robust domestic demand. Inflation was subdued, remaining well below the regional ceiling. The 2017 fiscal outturn and the 2018 budget are in line with the program targets and the goal of converging to the West African Economic and Monetary Union's regional fiscal deficit norm of 3 percent of GDP by 2019. The macroeconomic outlook is, however, subject to downside risks stemming mainly from Mali's fragile security situation.